On the n-fold pseudo-hyperspace suspensions of continua - Macias, Juan Carlos (Array, 2008)
Abstract: Let X be a (metric) continuum. Let n be a positive integer, let Cn(X) denote the space of all nonempty closed subsets of X with at most n components and let F1(X) denote the space of singletons. The n-fold pseudo-hyperspace suspension of X is the quotient space Cn(X)/F1(X). We present properties of this hyperspace